The Potential of Bioactive Compounds from Corn Silk (Zea mays L.) that Result from Gradual Fractionation Using Organic Solvents for the Use as a Natural Sunscreen - Laeliocattleya, Rosalina Ariesta; Prasiddha, Ismizana Jati; Estiasih, Teti; Maligan, Jaya Mahar; Muchlisyiyah, Jhauharotul (Fakultas Teknologi Pertanian Universitas Brawijaya, 2014)
The study aims to determine how the influence of the solvent on the content of bioactive compounds such as phenols, flavonoids, and carotene and also SPF (Sun Protection Factor) value on corn silk extract and how its potential for natural sunscreen. Dried corn silk was macerated using ethanol 96%, extract was fractionated then obtained extract from the fraction of: ethanol soluble (E1), ethanol soluble – n-hexane soluble (E2), ethanol soluble – ethyl acetate soluble (E3), and ethanol soluble – water soluble (E4). Total phenolic contents respectively was 34029.37 ± 1926.61 mg/kg; 358.28 ± 119.79 mg/kg; 9569.64 ± 1494.01 mg/kg; 41751.41 ± 1390.41 mg/kg. Total flavonoid contents respectively was 211.05 ± 3.73 mg/kg; 0 mg/kg; 36.31 ± 3.85 mg/kg; and 274.73 ± 9.24 mg/kg. Total carotene contents respectively was 11.3 ± 0.95 mg/kg; 434.68 ± 86.5 mg/kg; 41.18 ± 7.08 mg/kg; and 3.97 ± 0.41. SPF value determination by In Vitro spectrophotometry performed at two different concentrations (100 ppm and 1000 ppm), there are also controls in the form of commercial sunscreen (K1), β-carotene (K2), and quercetin (K3). The result showed that higher concentration resulted in a higher SPF value. SPF value (1000 ppm) consecutively was 17.30 ± 0.15; 9.97 ± 1.11; 25.38 ± 2.88; and 16.88 ± 2.09 and the controls consecutively was 31.00 ± 0.36; 39.35 ± 0.10; and 39.20 ± 0.06. The presence of various solvents influences on the content of bioactive compounds and also SPF values in each fraction. Although the SPF value from corn silk were lower compared to the controls. However, it is known that corn silk can be used for sunscreen as it belongs to type of ultra protection with SPF>15.Keywords: sunscreen, corn silk, bioactive compounds, SPF